Peningkatan Pemahaman Orang Tua Tentang Play Pretend - Siti Indatul Laili (Asthadarma : Jurnal Pengabdian Kepada Masyarakat, 2025)
During the toddler stage, children's play enters a phase where all play activities are done purely for fun and are not necessarily realistic. Toddlers consider their toys to be alive, like themselves, where toys can cry, laugh, get hungry, and more. The goal is to enhance understanding of pretend play. The implementation method includes preparation, implementation with pre-counseling evaluation of partners' understanding, counseling, and post-counseling evaluation. This community service activity was conducted in Dusun Wonoayu Timur, Dukuhmojo Village, Mojoagung District, Jombang Regency on October 16, 2024. Before the counseling, 14 (47%) partners had a good understanding of pretend play, and after the counseling, it increased to 30 (100%). This shows an improvement in participants' understanding of efforts to develop toddler curiosity in the era of Society 5.0 through pretend play activities. Through counseling, an educational approach can be implemented, enabling systematic, planned, and directed learning with active participation from individuals, groups, or communities to solve problems while considering socio-economic factors, leading to positive changes in individuals, groups, or communities.